Cultural-Pragmatic Features of Idioms and Their Translation Strategies - Islomova Navruza; Isakova Nodira Azzamovna (Indonesian Journal Publisher, 2026)
Idioms constitute a significant component of phraseological systems and represent fixed multi-word expressions whose meanings are not predictable from the semantic sum of their individual constituents. As culturally embedded linguistic units, idioms reflect the historical experience, worldview, social norms, and value systems of a speech community. This article examines the cultural and pragmatic dimensions of idiomatic expressions and analyzes principal strategies employed in their translation. Drawing upon established translation theories and comparative examples from English and other languages, the study highlights the challenges of achieving semantic, cultural, and stylistic equivalence. The findings demonstrate that effective idiom translation requires not only linguistic competence but also intercultural awareness and pragmatic sensitivity